Les inondations de février 2007 dans les kampung pauvres de Jakarta - Pauline Texier (EchoGéo)
The floods that affected Jakarta (20 M inhabitants) in February 2007 were catastrophic (55 human losses, 400,000 victims). Besides their intrinsic causes (favorable topographic context, concentration of precipitation in time, superposition of two flood waves), the inundation was amplified by the accelerated urbanization of these last ten years and by an inefficient water management at the city scale. This type of event mainly affected the poor districts, hence resulting in severe economical and sanitary consequences that might generate an increased vulnerability to flood hazards and a feeling of political insecurity for these populations